PEDAGOGICAL DESIGN IN DEVELOPING THE INFORMATION-CONSTRUCTIVE COMPETENCE OF FUTURE EDUCATORS - Olamova Mamura Umarovna (Bright Mind Publishing, 2025)
Today, the effective use of innovative technologies and pedagogical design methods at all levels of education, including preschool education, is of particular importance. This article analyzes the process of developing the information-constructive competence of future educators through pedagogical design technologies. It highlights ongoing reforms in the education system of the Republic of Uzbekistan, the introduction of digital technologies, and best practices aimed at improving the professional training of future educators. In addition, the article discusses pedagogical approaches focused on forming information-constructive competence, methodological recommendations, and ways to improve educational content.
Keywords: Pedagogical design, information-constructive competence, digital technologies, innovative education, preschool education, pedagogical methods.